Safety of deferasirox as an oral iron chelator in thalassemic children - Jaiswal, Shikha; Hishikar, Rajesh; Maheshwari, Basant; Khandwal, Onkar; Sheohare, Raka (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Thalassemia major patients require frequent blood transfusion leading to iron overload. Iron overload is characterized by excessive iron deposition and consequent injury and dysfunction of the heart, liver, anterior pituitary, pancreas, and joints. Because physiologic mechanisms to excrete iron are very limited, patients with iron overload and its complications need safe, effective therapy that is compatible with their coexisting medical conditions. Current prospective, observational study is done to assess the safety of deferasirox as an oral iron chelator, with specific reference to rise in serum creatinine level, alanine aminotransferase level (SGPT), urine albumin level in 50 multi-transfused thalassemia major children receiving deferasirox (DFX) therapy at registered thalassemia society Raipur, India. Methods: DFX was administered in an initial dose of 20 mg/kg/day and increased to a maximum of 40 mg/kg/day. Serum creatinine, alanine aminotransferase level (SGPT), urine albumin level were estimated in pretransfusion samples at time of registration and at 3 monthly intervals (4 times). The primary end point of the study was completion of 12 months of therapy (January 2013 to December 2013). Results: Prior to DFX therapy the mean serum creatinine, SGPT, urine albumin of all cases were 0.4617 mg/dl, 20.78 U/L and nil respectively. After 12 months of DFX therapy of mean dose 38 mg/kg/day, the mean serum creatinine was. 0.4624 mg/dL. SGPT was 20.81 U/L, and urine albumin was nil. Conclusions: Deferasirox monotherapy has a good safety profile and effectively chelates total body iron.